2005
DOI: 10.1124/jpet.104.082867
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Estrogenic Dilation of Rat Aorta Is Mediated Solely by Selective Estrogen Receptor-α Agonists and Is Abolished by Estrogen Deprivation

Abstract: Estrogen is known to induce rapid vasodilatory response in isolated arteries. Because estrogen is a nonselective receptor agonist, the involvement of estrogen receptor (ER) subtypes in acute estrogenic responses has remained elusive. Acute administration of the selective ER␣ agonist 4,4Ј,4Љ-(4-propyl-[ 1 H]pyrazole-1,3,5-triyl) tris-phenol (PPT) to precontracted aortic rings from intact female rats dose-dependently induced an ER-dependent vascular relaxation fully overlapping to that induced by 17␤-estradiol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
52
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 32 publications
6
52
1
2
Order By: Relevance
“…They observed that in rat aortic rings contracted with KCl, the ER-␤ agonist DPN produced significantly greater relaxations than the ER-␣ agonist PPT. In contrast, Bolego et al (6) reported that aortic rings isolated from E 2 -treated ovariectomized rats responded with higher potency to an ER-␣ agonist than an ER-␤ agonist. The apparent discrepancy between the results of Bolego et al (6) and our findings may be related to the use of different sexes, treatment regimen, and differences in ER-subtype predominance and/or connecting downstream mechanisms that can modify responses to ER agonists.…”
Section: Discussionmentioning
confidence: 93%
“…They observed that in rat aortic rings contracted with KCl, the ER-␤ agonist DPN produced significantly greater relaxations than the ER-␣ agonist PPT. In contrast, Bolego et al (6) reported that aortic rings isolated from E 2 -treated ovariectomized rats responded with higher potency to an ER-␣ agonist than an ER-␤ agonist. The apparent discrepancy between the results of Bolego et al (6) and our findings may be related to the use of different sexes, treatment regimen, and differences in ER-subtype predominance and/or connecting downstream mechanisms that can modify responses to ER agonists.…”
Section: Discussionmentioning
confidence: 93%
“…13 In this regard, we demonstrated previously that ER␣-selective agonists, unlike ER␤-selective agonists, induce acute vascular relaxation in the aorta from intact female or E 2 -replaced ovariectomized (OVX) rats. 7 Such an activity, however, is undetectable in preparations from untreated OVX rats, suggesting that physiological levels of circulating E 2 are essential for rapid vascular responses to be induced. 7,14 This likely occurs through regulation of the levels of ER and cellular effectors thereof, such as endothelial NO synthase (eNOS) after E 2 administration.…”
mentioning
confidence: 95%
“…12 The 2 ER isoforms not only are differentially modulated by circulating hormones but also mediate distinct actions in the vascular wall. In fact, ER␣ conveys both short-term effects including endothelial dilation 7 and long-term anti-inflammatory actions of E 2 . 13 In this regard, we demonstrated previously that ER␣-selective agonists, unlike ER␤-selective agonists, induce acute vascular relaxation in the aorta from intact female or E 2 -replaced ovariectomized (OVX) rats.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some flavonoids derived from natural compounds, such as genistein, daidzein, and apigenin, have been shown to compete with 17β-estradiol for binding to the estrogen receptor, acting as phytoestrogens (25). Thus, the vasorelaxant activities of Flavangenol may result from the activation of the estrogen receptor, which is known to induce the enhancement of the eNOS activity (26,27) and NO-mediated vasorelaxation (28). However, preincubation with the estrogen-receptor antagonist ICI 182,780 did not modify the vasorelaxant responses to Flavangenol.…”
Section: Enhancement Of Nos System By Flavangenolmentioning
confidence: 99%